2017
DOI: 10.1007/s12160-017-9918-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression Symptoms in Haemodialysis Patients Predict All-Cause Mortality but Not Kidney Transplantation: A Cause-Specific Outcome Analysis

Abstract: (ISRCTN06146268).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 37 publications
1
28
1
1
Order By: Relevance
“…But as with more recent studies, we were unable to confirm this association . As our patients with longer times to recover postdialysis also had higher self‐reported depression scores, and higher self‐reported depression scores are associated with increased risk of mortality . Then this may explain previous reports of an association between postdialysis recovery times and survival…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…But as with more recent studies, we were unable to confirm this association . As our patients with longer times to recover postdialysis also had higher self‐reported depression scores, and higher self‐reported depression scores are associated with increased risk of mortality . Then this may explain previous reports of an association between postdialysis recovery times and survival…”
Section: Discussioncontrasting
confidence: 79%
“…5,21 As our patients with longer times to recover postdialysis also had higher self-reported depression scores, and higher self-reported depression scores are associated with increased risk of mortality. 31 Then this may explain previous reports of an association between postdialysis recovery times and survival. 30 In our study, we found that patients who self-reported greater depression scores also reported longer postdialysis recovery times.…”
Section: Discussionmentioning
confidence: 64%
“…1,2 Although the absolute rates of clinically diagnosed depression are much lower, 3 self-reported depression is associated with increased over-all mortality. 4 A number of psychological theories, including human becoming theory, Bandura's self-efficacy theory, and Orem's self-care model, [5][6][7] have suggested that patients who take greater care of their own medical care have less depression and are more motivated to perform and promote activities designed to maintain or improve health care. 8 Indeed, studies in other chronic healthcare conditions, diabetes mellitus and congestive heart failure have reported that patients who take greater control of their own medical care [9][10][11][12] reported a reduction in emotional burden, 9 short-term improvement in glycaemic control, 10 over-all quality of life, 11 and shortterm changes in self-reported self-management skills predicted intermediate-term changes in improved mental quality of life and long-term changes in better physical quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence demonstrating the association between depression and mortality among individuals with End‐Stage Kidney Failure (ESKF). It is estimated that the presence of depressive symptoms is associated with a 50% increase in the risk of mortality . This is particularly concerning given the high prevalence of depression, which is estimated to be approximately between 23%‐39%, depending on whether diagnostic or screening tools are used for evaluation .…”
Section: Introductionmentioning
confidence: 99%